A Critical Review of Circular Economy Developments in European Union: Realities, Trends and Expectations - Iuliana NICOLAE; Jean Vasile ANDREI; Vasilii EROKHIN; Tianming GAO; Mehmet Emin KALGI (Communications of International Proceedings, 2022)
The circular economy and promotion of its specific mechanisms and principles constitute one of the fundamental steps in changing the classical economic paradigm and promoting some new principles, adapted to the new global transformations, in accordance with the achievement of a new sustainable economic growth. The central objective of this study circumscribes to and aims at the presentation of the actual stage of the development and application of the circular economy exigencies at the level of the European Union (EU), especially at the level of the states that have integrated in the last two waves and at emphasizing as much as possible some of the existing tendencies and challenges in the direction of adopting the circular economies practices. From this perspective, within the paper there are presented some reflections and approaches related to the tendency of the main indicators specific to the circular economy in the process of transition from the traditional linear economy, beside the manner in which they can interconnect and can relate to the new global challenges. The paper emphasizes as well the quantitative evolution of these analyzed specific indicators, constituting into a reference for the evaluation of the circular economy at the level of the EU, the analysis offering an analytical perspective over some possible evolutions and relevant implications on the implementation of the process of passing from the linear to the circular type within the contemporary European economies.
Keywords: circular economy; Sankey diagram; Circular Material Use Rate (CR); productivity; Raw Material Consumption (RMC); Domestic Material Consumption (DMC); material flows.